Integrating a Strategic Framework to Improve Health Education in Schools in South Tyrol, Italy - Christian J. Wiedermann; Patrick Rina; Verena Barbieri; Giuliano Piccoliori; Adolf Engl (MDPI AG, 2024)
This narrative review addresses the integration of health education into school curricula in South Tyrol, an Italian province with significant cultural and linguistic diversity. This review's objective is to analyze current health education initiatives and propose a strategic framework to enhance school-based health education, aiming to improve student well-being post-pandemic. The review synthesizes global examples and recent local studies, highlighting the importance of comprehensive teacher training, mindfulness-based interventions, culturally sensitive health education, and community engagement. The key findings indicate that current health education programs in South Tyrol are insufficient to meet immediate public health needs, such as low vaccine uptake and mental health challenges exacerbated by the COVID-19 pandemic. The proposed strategic framework seeks to align educational strategies with the diverse needs of South Tyrol's student population, thereby improving health literacy and behavior and strengthening the region's public health infrastructure.